THE INFLUENCE OF CO-CREATION, SERVICE QUALITY, AND QUALITY FUNCTION DEPLOYMENT ON SATISFACTION: EVIDENCE FROM APARTMENT HOUSING (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
This study aims to examine the influence of co-creation behavior, service quality, and the implementation of Quality Function Deployment (QFD) on resident satisfaction at Dian Regency Apartment Surabaya. The research employed a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to 175 residents and analyzed using Partial Least Squares (PLS). The findings reveal that co-creation behavior has a positive effect on service quality and the implementation of QFD. Furthermore, both service quality and QFD implementation significantly affect resident satisfaction. These results highlight that active resident involvement in co-creation enhances service quality and strengthens the effectiveness of QFD implementation, ultimately leading to higher satisfaction among apartment residents. The study contributes theoretically by integrating co-creation theory, SERVQUAL, and QFD in the context of vertical housing, while also providing practical implications for apartment management in developing resident-based service improvement strategies.
Keywords: Co-Creation; Service Quality; QFD; Resident Satisfaction; Apartment